PERAN ASOSIASI PETANI TEMBAKAU INDONESIA (APTI) DALAM MEMPERJUANGKAN KEPENTINGAN PETANI TEMBAKAU DI KABUPATEN TEMANGGUNG - Nurwiyati, Riris Tri; ., Yuwanto; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2017)
AbstractAssociation of Indonesian Tobacco Farmers (APTI) Temanggung as a container group offarmers in Temanggung Regency is expected to play an active role on what happens amongtobacco farmers. Through the implementation of targeted programs, improving the welfare oftobacco farmers in Temanggung Regency and their efforts in fighting for the interests of tobaccofarmers in Temanggung Regency can be realized. Targeted programs will also benefit theempowerment of the Indonesian Tobacco Farmers Association (APTI) Temanggung itself ..The purpose of this research is to know how APTI form and how to respond to TobaccoBill in Temanggung Regency. Know how the effectiveness of APTI's struggle in TemanggungRegency to protect their interestsTo answer the problem and purpose of this research, writer use qualitative descriptiveapproach. The results show the form and way of APTI struggle in responding to the draft law canbe seen from their action down the road peridoik and try to meet the members of the board andofficials who influence a policy.Over time APTI is expected to establish cooperation with more parties or tobaccoindustry companies and improve the ability of APTI Temanggung in order to maintain theexistence of APTI Temanggung and can be useful for farmers in Temanggung.Keywords: APTI, Role, Tobacco Farmer